2011
DOI: 10.1093/annhyg/mer069
|View full text |Cite
|
Sign up to set email alerts
|

Protective Facemask Impact on Human Thermoregulation: An Overview

Abstract: The use of protective facemasks (PFMs) negatively impacts respiratory and dermal mechanisms of human thermoregulation through impairment of convection, evaporation, and radiation processes. The relatively minor reported increases in core temperature directly attributable to the wearing of PFMs suggest that associated perceptions of increased body temperature may have a significant psychological component or that regional or global brain temperature changes are involved. Modifications in PFM structure, componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
60
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 81 publications
(86 reference statements)
1
60
0
1
Order By: Relevance
“…30 No significant differences in T chest and T aural between pregnant and non-pregnant subjects were noted (Table 1), and the minimal increases observed reflect that ~10% of body heat is normally dissipated by respiration, so that rebreathing expelled air from the N95 FFR deadspace has minimal effect on core temperature. 31 The significant effect of N95 FFR use on T chest ( P < .001) may indicate a greater effect of rebreathed warm air on the peripheral temperature of skin closest to the pulmonary system (ie, chest wall). 32 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 No significant differences in T chest and T aural between pregnant and non-pregnant subjects were noted (Table 1), and the minimal increases observed reflect that ~10% of body heat is normally dissipated by respiration, so that rebreathing expelled air from the N95 FFR deadspace has minimal effect on core temperature. 31 The significant effect of N95 FFR use on T chest ( P < .001) may indicate a greater effect of rebreathed warm air on the peripheral temperature of skin closest to the pulmonary system (ie, chest wall). 32 …”
Section: Discussionmentioning
confidence: 99%
“…The greater heat perception among all subjects when wearing an N95 FFR ( P ≤ .001) is likely related to the respirator’s barrier effects on facial skin heat loss mechanisms (evaporation, convection) and increased N95 FFR dead space temperature. 31 …”
Section: Discussionmentioning
confidence: 99%
“…The current study’s reported lower Δ values, when comparing respirator trials with controls, may be attributable to different mechanisms. The respiratory tract is responsible for 10–15 % of body heat elimination (depending on level of activity and environmental conditions) [6] and the use of N95 FFRs results in an increase in the respiratory rate and minute volume [18, 19], such that greater respiratory heat dissipation may account for our observed lower mean TMT Δ values with N95 FFR use. Similarly, the increased minute ventilation associated with pregnancy [20] would serve to augment respiratory heat dissipation and may have impacted the results in investigation b [12] where a downward trend in TMT from baseline is observed throughout the 1 h of N95 FFR wear compared with controls (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has shown that local alterations of facial, scalp and neck temperatures can impact TMT, presumably due to thermal effects on local dermal blood vessels that share circulation with vessels supplying the tympanic membrane [35]. Increased skin temperature, with concomitant warming of local dermal vessels in that area of the face covered by protective facemasks, results from a barrier effect upon local heat release mechanisms (i.e., facial skin heat convection, radiation and sweat evaporation) and from the trapping of warmed exhaled air in the mask deadspace [68]. Therefore, it is plausible that the TMT of patients wearing protective facemasks may be elevated over baseline values and thus negatively impact the clinical utility of the measurements.…”
Section: Introductionmentioning
confidence: 99%
“…regards thermal discomfort that is manifested as subjective impressions of increases in facial warmth or total body heat [13]. This is an important issue given that thermal intolerance to protective facemasks impacts compliance and, by extension, protection [3].…”
Section: Introductionmentioning
confidence: 99%